AUDIT OF DIAGNOSIS AND MANAGEMENT OF PNEUMOTHORAX AT AL SHAAB TEACHING HOSPITAL - Omer Elgaili Yousif ELHAG; Yousif Omer Elgaili YOUSIF; Amro Abdalmageed Altayeb MOHAMED (Buletinul Academiei de Ştiinţe a Moldovei: Ştiinţe Medicale, 2022)
Introduction. A pneumothorax is defined as the presence of air within the pleural cavity, it is classified as spontaneous primary or secondary and traumatic iatrogenic and non-iatrogenic. Despite having Sudan national protocol for the management of pneumothorax, there appears to be wide variation in clinical practice in diagnosis and management of pneumothorax Aims and objectives. The audit aims to study the initial management of primary and secondary pneumothorax at Al SHAAB teaching hospital. Method. Data collection was made from patients’ records with a diagnosis of pneumothorax Results. Fifty-five patients who were admitted to the chest department were enrolled. The majority of patients were between 25-45 years of age (40%), male with a female ratio of 3:1. The main presenting symptoms were cough 50 (94.4%) and shortness of breath 44(80%) followed by chest pain 20(36.4). Twenty patients (36.4) were a smoker and 35 (63,.6%) were a non-smoker. Pulmonary tuberculosis is the leading cause of pneumothorax 33(60,1%) and bronchial asthma 4(7.3%) while primary spontaneous were 9(16.4%). Clinically and radiologically the right side is more affected than the left side 34(61.8%) and 19(16.4%) respectively, pure pneumothorax in29 (52.7%) and hydropneumothorax in 26(37.3%). The size of pneumothorax is large in 25 (45.5%), medium18 (32.7), and small in 12(21.8%). Thirty-nine (70.9%) were managed with chest tube thoracostomy, 12 (21.8) by simple aspiration, and 4 (7.3%) responded to the observation of patients for two weeks. Conclusion. There is suboptimal compliance to the Sudan protocol in the management of pneumothorax. Recommendations. We recommended federal ministry of health to avail the protocol of diagnosis and management of pneumothorax in all emergency departments, also we recommended training of all registrars of chest medicine in the protocol of diagnosis and management of pneumothorax.